The relationships between technological turbulence, flow experience, innovation performance and small firm growth - Slavec Gomezel, Alenka; Aleksić, Darija (Journal of Business Economics and Management, 2020)
The main objective of the paper is to address the question of how to foster innovation and small firm growth under different levels of technological turbulence. Specifically, the paper examines the relationship among risk-taking, arising from different levels of technological turbulence, flow experience, innovation and small firm growth (i.e. market share and ROI growth). The underlying premise of our research is that there are substantial differences in low and high technological environments in terms of the relationships of risk taking, flow at work, innovation and small firm growth. Based on a survey among 188 entrepreneurs, the paper tests the proposed relationships in technological diverse environments with structural equation modelling. The results show that, when the level of technological turbulence is high, flow experience is significantly related to innovation and small firm growth, while in low-technological turbulence environment such relationships are not present. The study contributes to the entrepreneurial literature by demonstrating that in highly turbulent environments, flow experience may promote entrepreneurs’ innovation and the efficiency of small firm performance. The study also provides new empirical insights about the relationship between entrepreneurs’ behaviour, which is influenced by environmental conditions, on the one hand and innovation and small firm growth on the other hand.